Colonising antinormative sex: The flexibility of post-porn heterosex in random webcam sex. (June 2018) - Gregory, Tim
Random webcam encounters first came into popular consciousness with the rise of Chatroulette in 2009. Since then, various websites have emerged based on a similar model, catering specifically to webcam based sexual practices. This article focuses on one of these sites, Dirtyroulette, and argues that it is an example of what I am calling 'post-porn heterosex'—defined by the increasing acceptance of pornography into heterosex. An examination of the dialectics of engagement on Dirtyroulette—the complex navigation of public and private, boredom and attention, exhibitionism and voyeurism, signal and noise, and randomness and consistency—reveals how users perform post-porn sex acts. For Dirtyroulette users the normative is not opposed to the nonnormative, and sex acts which appear transgressive or homosocial may be demonstrating how heterosex colonises emergent sexual practices and spaces. This article speculates as to why the site is not a space for antinormative sex, and why the majority of sex acts should be considered as post-porn heterosex. Dirtyroulette demonstrates that post-porn heterosex is more fluid than the public, symbolic and static images of heterosex that form the foundation of heterosexuality's 'natural' claims. This article asks: Does the visibility of Dirtyroulette provide a potential rupture in heterosex—does it produce opportunities in which the 'natural' claims of heterosex are contradicted by an image that is not fixed and does not have a foundational orientation? Or is a correlation between the symbolic image of heterosex and the gestures of heterosex no longer required for the maintenance of heterosexual culture?